Insight into the effects of moisture and layer build-up on the formation of lead soaps using micro-ATR-FTIR spectroscopic imaging of complex painted stratigraphies - Possenti, Elena (Anal Bioanal Chem, 2020)
Metal soaps are formed in paint layers thorough the reaction of metal ions of pigments and fatty acids of organic binders. In this study, micro-ATR-FTIR spectroscopic imaging was used to analyse the formation of lead soaps in oil-based paint layers in relation to their exposure to moisture sources. The investigations were carried out on authentic samples of complex stratigraphies from cold painted terracotta statues (Sacred Mount, Varallo, UNESCO) and different IR-active lead white pigments, organic materials, and lead soaps were discriminated. The saponification of selected paint layers was correlated to the conservation history, the manufacturing technique, and the build-up of layers. The presence of hydrophilic layers within the stratigraphy and their role as a further water source are discussed. Furthermore, the modifications experienced by lead-based pigments from the core of an intact grain of pigment towards the newly formed decay phases were investigated via a novel approach based on shift of the peak for the corresponding spectral bands and their integrated absorbance in the ATR-FTIR spectra. Qualitative information on the spatial distribution from the chemical images was combined with quantitative information on the peak shift to evaluate the different manufacture (lead carbonate, basic lead carbonate) or the extent of decay undergone by the lead-based pigments as a function of their grain size, contiguous layers, and moisture source. Similar results, having a high impact on heritage science and analytical chemistry, allow developing up-to-date conservation strategies by connecting an advanced knowledge of the materials to the social and conservation history of artefacts. [Image: see text] SUPPLEMENTARY INFORMATION: The online version of this article (10.1007/s00216-020-03016-6) contains supplementary material, which is available to authorized users.